Anthropometric Markers and Iron Status of 6–12-Year-Old Thai Children: Associations and Predictors. (13th April 2021) - Suteerojntrakool, Orapa; Khongcharoensombat, Tharida; Chomtho, Sirinuch; Bongsebandhu-phubhakdi, Chansuda; Tempark, Therdpong; Fewtrell, Mary
Abstract : Introduction . Obesity may be associated with poor iron status. The objective of this study was to investigate the association between different indices of iron status and anthropometric measurements in Thai children. Materials and Methods . Anthropometry (weight, height, waist circumference (WC), and body composition assessed by bioelectrical impedance analysis) and iron indices were measured in 336 Thai children aged 6–12 years. Iron deficiency (ID) was defined using two or more of the following: (1) %transferrin saturation (%Tsat) < 16%; (2) serum ferritin (SF) < 15  μ g/mL; and (3) soluble transferrin receptor (sTfR) > 5 mg/L. Iron deficiency anaemia (IDA) was defined as haemoglobin < WHO age cutoff combined with ID. Overweight and obesity were defined as body mass index (BMI) standard deviation score (SDS) ≥ +1 SDS or +2 SDS, respectively (WHO growth reference). Results . BMI SDS was significantly positively correlated with sTfR and SF (sTfR, r : 0.209, p  < 0.001; SF, r : 0.214, p  < 0.001) and negatively correlated with %Tsat ( r : −0.132, p  = 0.013). Correlations between WC SDS and %fat mass and each iron marker were similar. The percentage with low SF was significantly lower than that using other individual markers. ID prevalence was not significantly different between normal-weight and overweight/obesity groups although a significantly higher proportion of overweight/obese children had sTfR >5 mg/L. Puberty and menarche were significant predictors of ID (puberty adjusted OR: 2.20, 95% CI: 0.43, 11.25; menarche adjusted OR: 6.11, 95% CI: 1.21, 30.94). Conclusion . Greater adiposity was associated with poorer iron status. However, SF may not be a good indicator of iron status in Thai children, particularly in those who are overweight/obese, whereas sTfR merits further investigation.